2010
DOI: 10.1007/s11745-010-3513-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein(a) Levels are Greater in Female than Male Patients with Type‐2 Diabetes

Abstract: Women with diabetes are faced with a higher risk of dyslipidemia and cardiovascular disorders than men with diabetes. We aimed to study the role of gender and menopausal status in serum Lp(a) levels in patients with type 2 diabetes. We quantified serum Lp(a) levels in a group of 477 patients with type 2 diabetes (men, premenopausal and postmenopausal women with diabetes), as well as in 105 controls. We stratified the patients into two groups of low Lp(a) levels (Lp(a) <35 mg/dl) and elevated Lp(a) levels (Lp(a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…This is confirmed in our study since the cohort of diabetic woman show worse parameters that diabetic males except for the cholesterol-HDL as already reported (Wannamethee et al, 2011). It is indeed well established that post-menopausal women are more prone to dyslipidemia as well as to an increased risk of mortality for cardiovascular diseases (Kautzky-Willer et al, 2010;Nakhjavani et al, 2011). The reason for this is not clear but it is possible that diabetes has a greater adverse effect in cardiovascular risk factors (Wannamethee et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…This is confirmed in our study since the cohort of diabetic woman show worse parameters that diabetic males except for the cholesterol-HDL as already reported (Wannamethee et al, 2011). It is indeed well established that post-menopausal women are more prone to dyslipidemia as well as to an increased risk of mortality for cardiovascular diseases (Kautzky-Willer et al, 2010;Nakhjavani et al, 2011). The reason for this is not clear but it is possible that diabetes has a greater adverse effect in cardiovascular risk factors (Wannamethee et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Early studies re ported elevated Lp(a) concentrations in patients with type 1 diabetes mellitus (IDDM) (225)(226)(227)(228)(229)(230), as well as in pa tients with type 2 diabetes mellitus (NIDDM) (231,232). Furthermore, some recent studies in Asian populations report an association between an elevated Lp(a) concen tration and incident NIDDM (233)(234)(235). Rainwater et al (236) reported significantly lower Lp(a) concentrations in NIDDM patients compared with matched nondiabetic controls in the San Antonio Heart Study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in cases of surgical menopause, a significant increase in Lp(a) concentrations is already noticed 3 months after oophorectomy . However, few studies have directly compared Lp(a) concentrations between pre‐ and postmenopausal women . In the majority of them, postmenopausal women had higher Lp(a) compared with premenopausal, as well as with perimenopausal women .…”
Section: Menopause and Lp(a): Is There A Link?mentioning
confidence: 99%
“…Moreover, oxidative compounds, such as oxidised phospholipid (OxPL), non‐covalently bound to apoB‐100, are also key mediators for the role of Lp(a) in the atherosclerotic process . However, despite the independent association of Lp(a) concentrations with increased prevalence of CVD, few studies have assessed its role in menopause‐related CVD risk, seeking for differences between pre‐ and postmenopausal women …”
Section: Introductionmentioning
confidence: 99%